2018
DOI: 10.1093/jmicro/dfy027
|View full text |Cite
|
Sign up to set email alerts
|

Development of a three-dimensional tomography holder for in situ tensile deformation for soft materials

Abstract: An in situ straining holder capable of tensile deformation and high-angle tilt for electron tomography was developed for polymeric materials. The holder has a dedicated sample cartridge, on which a variety of polymeric materials, such as microtomed thin sections of bulk specimens and solvent-cast thin films, can be mounted. Fine, stable control of the deformation process with nanoscale magnification was achieved. The holder allows large tensile deformation (≃800 μm) with a large field of view (800 × 200 μm bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Herein, we used in situ transmission electron microscopy (TEM) to study the deformation and fracture processes of a glassy epoxy film containing independently dispersed silica nanoparticles during the stretching process. 20–22 We first confirmed the wide area of deformation for the epoxy nanocomposite film in which a crack propagated. This enabled us to evaluate (1) how a silica nanoparticle affected crack propagation and (2) how a nanovoid was formed in close proximity to the epoxy/silica interface.…”
mentioning
confidence: 71%
“…Herein, we used in situ transmission electron microscopy (TEM) to study the deformation and fracture processes of a glassy epoxy film containing independently dispersed silica nanoparticles during the stretching process. 20–22 We first confirmed the wide area of deformation for the epoxy nanocomposite film in which a crack propagated. This enabled us to evaluate (1) how a silica nanoparticle affected crack propagation and (2) how a nanovoid was formed in close proximity to the epoxy/silica interface.…”
mentioning
confidence: 71%
“…25,26 We recently developed a tensile holder for TEM, which enables us to stretch polymeric samples without the field of view drifting, and directly observed the morphological changes of a nanoparticle-filled rubber (similar one used in the present sample) using this. 27 In the present study, local deformation behavior, namely, the nanoscale strain behavior, were clarified for the first time in a nanoparticle-filled rubber under tensile deformation based on in situ TEM observation. The finite element method (FEM) was used together with the TEM results to simulate the local stresses in nanoparticle-filled rubber for the first time, which revealed the reinforcing mechanism of the added nanoparticles under deformation.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Because of the lack of appropriate means to observe rubber materials under deformation with TEM, few in situ nanoscale observations of these materials have been reported. Recently, a TEM holder was developed that enables the stretching of rubber materials during TEM observation, 20,59,60 with which nanoscale deformation behaviors in a silica nanoparticle‐filled rubber were successfully observed. It was observed that strain propagates along the network of silica aggregates.…”
Section: Introductionmentioning
confidence: 99%